PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI FASE F SMA NEGERI 2 KOTO BARU DHARMASRAYA - Gundra, Gundra (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students must develop the capacity to solve mathematical problems well. The main goal for students studying mathematics is to develop this talent. However, grade XI students at SMA Negeri 2 Koto Baru still have a poor level of competence. Educators' failure to implement effective learning strategies to enhance this aptitude is the root cause of this problem. Think Talk Write (TTW) is one of the cooperative learning strategies that can help students to improve these abilities. This study used a quasi-experimental design. The t-test results showed a P-value = 0.000 which means the null hypothesis (H0) cannot be accepted. The TTW model appears to be more effective learning conventional forms.Keywords– Cooperative Learning, Problem-Solving Abilities,  Think Talk Write